Corrosion of orthodontic brackets in different spices:In vitro study - T P Chaturvedi (Wolters Kluwer Medknow Publications, 2014)
Context: Moist environment in the mouth varies and causes variable amounts of corrosion of dental materials. This is of concern particularly when metallic implants, metallic fillings, orthodontic appliances are placed in the hostile electrolytic environment in the human mouth. Components of diet rich in salt and spices are important factors influencing the corrosion of metallic appliances placed in the oral cavity. Aims: To study in vitro corrosion of orthodontic metallic brackets immersed in solutions of salt and spices in artificial saliva. Materials and Methods: Orthodontic brackets were used for corrosion studies in artificial saliva, salt, and spices using electrochemical technique and surface analysis. Electrochemical studies using different parameters were done in solutions of artificial saliva containing salt and spices. Photomicrographs from the optical microscope were also obtained. Results: Results of corrosion studies have clearly demonstrated that certain spices such as turmeric and coriander are effective in reducing corrosion, whereas salt and red chili have been found to enhance it. Surface analysis of small pits present on the surface of the as-received bracket will initiate corrosion which leads to more pitting.